2020
DOI: 10.1097/cnj.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

The Greatest of These

Abstract: Nurses have put themselves in precarious situations by caring for COVID-19 patients. Through the grid of faith, hope, and love as depicted in 1 Corinthians, the author commends the selfless work of nurses and esteems God's faithfulness to nurses who acknowledge him.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Nelan (2020) , by working during the pandemic, Christian healthcare workers have demonstrated the presence of Christ, exemplifying character traits of faith, hope, and love that will endure beyond this current storm of the COVID-19 pandemic. Protecting healthcare workers' well-being through appropriate measures is crucial in a national emergency public health response ( Shaukat et al, 2020 ).…”
Section: Faith During a Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nelan (2020) , by working during the pandemic, Christian healthcare workers have demonstrated the presence of Christ, exemplifying character traits of faith, hope, and love that will endure beyond this current storm of the COVID-19 pandemic. Protecting healthcare workers' well-being through appropriate measures is crucial in a national emergency public health response ( Shaukat et al, 2020 ).…”
Section: Faith During a Pandemicmentioning
confidence: 99%
“…According to Nelan (2020), by working during the pandemic, Christian healthcare workers have demonstrated the presence of Christ, exemplifying character traits of faith, hope, and love that will endure beyond this burnout during the COVID-19 pandemic (Lao et al, 2020). Early studies support that nearly half of nurses reported high levels of burnout during the first wave of the pandemic (Matsuo et al, 2020).…”
Section: Faith During a Pandemicmentioning
confidence: 99%